Association between the variability of non-high-density lipoprotein cholesterol and the neutrophil-to-lymphocyte ratio in patients with coronary heart disease - Chen, Yifan; Zhang, Sisi; Tao, Yecheng; Hu, Wenyi; Li, Duanbin; Shen, Xiaohua; Li, Ya; Lin, Maoning; Zhang, Wenbin; Liu, Xianglan; Xie, DaQi (Frontiers in Cardiovascular Medicine, 2023)
Lowering lipid variability may be a potential strategy for improving the inflammatory state in patients with coronary heart disease (CHD). This study aims to investigate the association between the variability of non-high-density lipoprotein cholesterol (non-HDL-C) and the neutrophil-to-lymphocyte ratio (NLR).This study enrolled 2711 CHD patients subjected to percutaneous coronary intervention (PCI). During the 1-year follow-up period after PCI, the variability of non-HDL-C is assessed using standard deviation (SD), coefficient of variation (CV), and variability independent of mean (VIM). NLR is calculated as the ratio of absolute neutrophil count to absolute lymphocyte count. The relationship between non-HDL-C variability and average NLR levels during follow-ups was examined using linear regression analysis.The age of the patients was 64.4±1 0.8 years, with 72.4% of the patients being male.The average NLR level was 2. 98 [2.26, 4.14] during the follow-up (1-year after PCI).